DEVELOPMENT OF INFRASTRUCTURE, SOCIAL, & ECONOMY IN DEVELOPING VILLAGE (Study in Penatarsewu Village, Tanggulangin Sub-District, Sidoarjo Regency - Durratun Nashihah (Ikatan Dosen Menulis, 2023)
Due to a variety of causes, several settlements in the Sidoarjo Regency can be classified as developing. The first problem is infrastructure. In Penatarsewu Village, Tanggulangin District, there are many poor educational circumstances, especially in public primary schools. The second problem is a lack of community involvement in development. In this scenario, physical development is not always handled by the village council; locals can also get engaged by building village roads and fields. Another issue is the absence of Village-Owned Enterprises (BUMDes). The two research goals of this study, which uses qualitative technique and descriptive research, are the development of infrastructure, society, and the economy in developing villages. The Miles, Huberman, and Saldana model serve as the foundation for this study's data analysis technique Interviews, observation, and documentation were used as data gathering techniques in this study. The results of this study imply that in growing villages, infrastructure, social, and economic growth have not yet been fully realized and compatible. Infrastructure development, including the construction of roads and educational institutions, is an area where it is improperly carried out and incompatible. between village heads and local authorities when the development plans were submitted. The bulk of the classrooms at the school are in poor condition because of wall damage that has continued despite multiple restorations, and the teachers' inability to effectively instruct the pupils is the empowerment for the development of society.